The formation of professional preferences among high school students in Kazakhstani schools (The Journal of Psychology and Sociology, 2024)
​The choice of future profession is an important stage in the life of every high school student. Changes in the labor market transform models and methods of career selection which lead to changes in the professional preferences of young people. Throughout the career decision-making process, high school students may encounter conflicts between their interests, personal plans, and external circumstances. The article provides insights from a sociological study conducted among high school students. The study aims to examine the process of forming professional preferences of high school students. The sample size is 558 high school students. The socio-demographic structure of the respondents covers all important characteristics such as gender, type of school, nationality, and place of residence. According to the results obtained, the majority of students have made some degree of determination regarding their professional choice. The influence of career guidance work is evident in making decisions about future professions. High school students who independently undergo career guidance activities show comparatively high decisiveness in comparison with high school students who are limited to career guidance activities within the school. Most high school students have seen changes in their professional preferences over the past three years, largely influenced by shifts in the labor market and guidance from parents, teachers.The data obtained can be used to optimize the organization of career guidance work in schools and to forecast the professional choices of school youth. The theoretical significance is associated with a deeper understanding of the process of forming professional preferences of high school students, taking into account various factors and decision-making about profession choice.Keywords: profession, professional preferences, type of school, state school, labor market, career guidance work.